Cajal outside the laboratory - Valega, Juan Francisco (1952)
We could not miss in the remembrance that we are doing the Life and Work of Santiago Ramón y Cajal, are the occasion of his centenary, some notes or notes, or variations if you will, on the sage outside the laboratory.